Junior High School Students' Science Literacy Skills based on the Nature of Science Literacy Test (NOSLiT) - Abdul Kadir; Zulqarnain T; Amiruddin Takda; Jahidin; Muhammad Shaleh Assingkily; Mustapa Ahmad (Jurnal Pendidikan IPA Indonesia, 2025)
Science literacy is a fundamental competency for students to engage with scientific issues and make evidence-based decisions. However, Indonesian students consistently rank low in international assessments such as PISA, revealing major gaps in their ability to understand and apply scientific concepts. This study aims to measure the science literacy skills of junior high school students using the Nature of Science Literacy Test (NOSLiT), which focuses on students' understanding of the nature and processes of science rather than solely content mastery. A descriptive quantitative method was employed with 150 ninth-grade students from five public junior high schools in Bombana Regency, Indonesia. The NOSLiT instrument, adapted to the Indonesian context, consists of 35 multiple-choice items across five science literacy domains. Results indicated that students' overall performance was categorized as very poor, with an average score of 39.7%. Key weaknesses were found in scientific thinking, societal application of science, and scientific methodology. These findings highlight a mismatch between current teaching practices and the demands of 21st-century science education. The study underscores the importance of integrating inquiry-based and contextually relevant pedagogy to enhance students' scientific reasoning, curiosity, and literacy. This research provides a foundation for curriculum development and targeted interventions aligned with Sustainable Development Goal 4 on quality education.